Analyzing the use of fact-checking tools in disaster-risk reduction in Europe through the lens of the heuristic-systematic model - Nadejda Komendantova; Tahereh Zobeidi; Masoud Yazdanpanah (Scientific Reports)
Abstract Journalists, emergency responders, and the general public facing natural and anthropogenic disasters frequently disseminate emergency information via social media. The spread of fake news during disasters can, however, disrupt the crisis management process and increase victim numbers. Identifying false information can curb its spread and reduce its impact on people’s attitudes and behaviors. Understanding how and why people in a disaster situation use fact-checking tools is crucial, as disaster-risk messages containing false content can usually be detected using systematic or heuristic processing. This study applies the heuristic-systematic model (HSM) to analyze social media users’ intention to use fact-checking tools. The empirical study data derived from 202 questionnaires collected through an online survey of residents of countries of the European Union. The results of structural equation modeling show the credibility of using HSM to analyze the intention to use fact-checking tools. About 33% of the changes in people’s intention to use fact-checking tools are predicted by this model. This study has implications for the use of theoretical models in communication science to predict intention to use fact-checking tools in disaster risk-reduction situations.